Archaeological Interventions in Medieval Jewish Cemeteries in Western Europe - Philippe Blanchard; Jérôme Livet; Valentina Di Stefano (Fasciculi Archaeologiae Historicae)
This article presents the main Jewish cemeteries of the Medieval period that have been the object of archaeological intervention in several countries of Western Europe (France, Spain, England, Italy, Switzerland). The objective is to synthesise the information from each site in order to highlight the main characteristics and recurring points.